Meningkatkan Ekosistem Digitalisasi Ekonomi Syariah pada Santri Dar El Istiqomah Serang - Sagantha, Fitri; Gustiana, Restia; Ulfa, Maria (Prodi Ekonomi Syariah Universitas Pamulang, 2023)
The global market for the Islamic economic and financial sector continues to grow in line with the increasing number of world Muslims. In 2019, it was recorded that 1.9 billion Muslims around the world spent US2.02 trillion to meet their needs for products that comply with sharia principles. This market is an opportunity that we need to optimize by developing the Islamic economy and finance in the country and opening access to marketing Indonesian halal products in the global market. This progress has been well received by Islamic finance industry players to continue to compete, including in accommodating MSMEs in this country. Ultimately, competitors in the digital sharia field are transformed into an ecosystem that continues to morphose to meet the needs of the Muslim community in the country in the halal financial industry. This service method is carried out by socializing the Sharia Economic Digital Ecosystem with the participants. The results of community service are not only by providing input in the form of understanding but in the form of training which will later be able to produce output in the form of improving the ecosystem which can be seen in the final stage of PKM, namely evaluation. With the Socialization of the Digital Ecosystem of the Sharia Economy at Dar el Istiqomah Islamic Boarding School students, it is hoped that the students can understand the concept of the Digital Sharia Economy and can slowly apply the concept of Islamic Economics in their daily lives.